2023
DOI: 10.1111/jocd.15588
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and hormonal abnormalities in adult female acne

Abstract: Acne is a chronic inflammatory disease of pilosebaceous unit characterized by formationof comedones, papules, pustules, and nodules of varying degree of inflammation and depth. 1 It is principally a disorder of adolescence. However, the prevalence of adult patients with acne is increasing and women comprise majority of cases. Adult acne is defined as acne that develops (late-onset acne) or continues (persistent acne) after 25 years of age. 2 Increased sebum production, follicular hyperkeratinization, Propionib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(124 reference statements)
0
0
0
Order By: Relevance
“…The study by Meena et al revealed an elevated prolactin serum level in 2 out of 60 acne patients (3.3%). Moreover, 6.7% of patients presented a raised total testosterone level [ 32 ]. In the study by Dhaher et al, in up to 32% of patients with acne, the measured prolactin serum level was above the normal range [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Meena et al revealed an elevated prolactin serum level in 2 out of 60 acne patients (3.3%). Moreover, 6.7% of patients presented a raised total testosterone level [ 32 ]. In the study by Dhaher et al, in up to 32% of patients with acne, the measured prolactin serum level was above the normal range [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was no correlation between the hormone level and acne severity [ 30 ]. In the study by Meena et al, elevated LH and FSH serum levels were found in 3.3% and 18.3% of acne patients, respectively [ 32 ]. The study by Khunger et al revealed an elevated LH serum level in 2 out of 280 patients and a decreased FSH serum level in 1 patient.…”
Section: Discussionmentioning
confidence: 99%